2017
DOI: 10.1248/bpb.b17-00479
|View full text |Cite
|
Sign up to set email alerts
|

Active Ingredients of Hange-shashin-to, Baicalelin and 6-Gingerol, Inhibit 5-Fluorouracil-Induced Upregulation of CXCL1 in the Colon to Attenuate Diarrhea Development

Abstract: 5-Fluorouracil (5-FU)is widely used as an anti cancer drug and is known to cause severe diarrhea. Recently we suggested that levels of chemokine (C-X-C motif) ligand 1 (CXCL1) and neutrophil recruitment in the colonic mucosa were drastically increased by the 5-FU administration in mice. Hange-shashin-to (HST) is prescribed in Japan for treat gastritis, stomatitis, and inflammatory diarrhea. We therefore examined the effects of HST and its active ingredients on 5-FU-induced CXCL1 upregulation in cultured colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The findings demonstrated that BXD, particularly baicalein and 6-gingerol, decreased the mRNA expression of CXCL1 via activating NF-κB in vitro, and attenuated the development of neutrophil recruitment and 5-FU-induced diarrhea in vivo. [ 94 ]…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…The findings demonstrated that BXD, particularly baicalein and 6-gingerol, decreased the mRNA expression of CXCL1 via activating NF-κB in vitro, and attenuated the development of neutrophil recruitment and 5-FU-induced diarrhea in vivo. [ 94 ]…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…Harati et al (2017) documented that EGCG and silibinin represent potential candidate molecules as mild therapeutic options for patients with solid sarcomas that require palliative treatment and are not suitable for doxorubicin-based chemotherapy [207]. In another preclinical study, baicalelin and 6-gingerol reduced 5-fluorouracil-induced overexpression of CXCL1 in the colon and prevented the development of neutrophil recruitment and weakened diarrhea development by the suppression of NF-κB activity [208]. Data from another preclinical study point out to protective role of quercetin coadministered with vitamin E in the prevention of doxorubicin-induced toxicity in uterine and ovarian tissues in rats [209].…”
Section: Exemplified 3pm Pathwaysmentioning
confidence: 99%
“…Hangeshashinto is a traditional Japanese herbal medicine used for diarrhea, anorexia, nausea, and vomiting [7][8][9][10][11][12]. This herbal medicine may cause pseudo-hyperaldosteronism and skin rash, but their frequency is low, and serious adverse events are extremely rare [13].…”
Section: Introductionmentioning
confidence: 99%